Diversity of root-endophytic Trichoderma from Malaysian Borneo - Cummings, N. J.; Ambrose, A.; Braithwaite, M.; Bissett, J.; Roslan, H.A.; Abdullah, J.; Stewart, A.; Agbayani, F. V.; Steyaert, J.; Hill, R. A. (German Mycological Society and Springer-Verlag Berlin Heidelberg, 2016)
Trichoderma species form endophytic associations with plant roots and may provide a range of benefits to their hosts. However, few studies have systematically examined the diversity of Trichoderma species associated with plant roots in tropical regions. During the evaluation of Trichoderma isolates for use as biocontrol agents, root samples were collected from more than 58 genera in 35 plant families from a range of habitats in Malaysian Borneo. Trichoderma species were isolated from surface-sterilised roots and identified following analysis of partial translation elongation factor-1α (tef1) sequences. Species present included Trichoderma afroharzianum, Trichoderma asperelloides, Trichoderma asperellum, Trichoderma guizhouense, Trichoderma reesei, Trichoderma strigosum and Trichoderma virens. Trichoderma asperellum/T. asperelloides, Trichoderma harzianum s.l. and T. virens were the most frequently isolated taxa. tef1 sequence data supported the recognition of undescribed species related to the T. harzianum complex. The results suggest that tropical plants may be a useful source of novel root-associated Trichoderma for biotechnological applications.